IDENTIFIKASI SOLUSI KONTRAKTOR TERHADAP PENERAPAN GREEN CONSTRUCTION PADA INDUSITRI KONSTRUKSI DI BALIKPAPAN - Syafira Vesseli Nata; Oryza Lhara Sari (INFO-TEKNIK, 2022)
The green construction concept design in the scope of civil buildings has the potential and effectiveness to reduce environmental damage. In order for the Green Construction concept to be implemented, it needs to be disseminated to contractors. The understanding of the parties needs to be known to determine the readiness to follow up on the concept. This study aims to determine the solutions that can be given to apply the concept. The most dominant solution is 93.3%, namely Building a building system that is efficient in using energy.. This research can be the basis for further research on green construction in the Construction Industry